Rapid Ultrasound for Shock and Hypotension: A Clinical Update for the Advanced Practice Provider. (October 2020) - Gonzalez, Juan M.; Ortega, Johis; Crenshaw, Nichole; de Tantillo, Lila
Abstract : The Rapid Ultrasound for Shock and Hypotension (RUSH) examination is used for patients with hypotension without clear cause or undifferentiated hypotension. In the emergency department setting, clinicians may perform the RUSH examination to supplement the physical assessment and differentiate the diagnosis of hypovolemic, obstructive, cardiogenic, and distributive forms of shock. The key elements of the RUSH examination are the pump, tank, and pipes, meaning potentially causes of the hypotension are examined within the heart, vascular volume and integrity, and the vessels themselves. Clinicians follow a systemic protocol to seeking evidence of specific conditions including heart failure exacerbation, cardiac tamponade, pleural effusion, pneumothorax, abdominal aortic aneurysm, and deep vein thrombosis. Because ultrasonography is a user-dependent skill, the advanced practice nurse in the emergency department should be educated regarding the RUSH protocol and prepared to implement the examination.